Association between coffee and incident heart failure: A prospective cohort study from the UK Biobank - Han, Qiang; Chu, Jiadong; Hu, Wei; Liu, Siyuan; Sun, Na; Chen, Xuanli; He, Qida; Feng, Zhaolong; Li, Tongxing; Wu, Jun; Shen, Yueping (Nutrition, metabolism, and cardiovascular diseases, 2023)
The relationship between coffee consumption and heart failure (HF) incidence is inconclusive. This study aimed to explore the association between time-varying coffee consumption and incident HF using a longitudinal study design. Data were obtained from the UK Biobank, comprising 497,503 adults (age, 56.5 ± 8.1 years; 54.6% women) who were free from HF at baseline in 2006–2010. The median follow-up time for the HF incidence was 11.9 years. Marginal structural models (MSM) were employed to adjust for potential time-varying confounders and account for bias caused by loss of follow-up. Furthermore, we used a restricted cubic spline to test and describe the nonlinear relationship between coffee consumption and HF risk. At baseline, 70.5% of participants reported drinking ≥1 cups/d coffee and 2.7% participants developed HF. After adjusting for potential confounders, we identified a nonlinear J-shaped association between coffee consumption and HF risk (P < 0.001). Compared with drinking coffee <1 cups/d, 1–2 cups/d (HR = 0.878; 95% CI: 0.838–0.920), 3–4 cups/d (HR = 0.920; 95% CI: 0.869–0.974) may be associated with a reduced risk of HF, while >6 cups/d (HR = 1.209; 95% CI: 1.056–1.385) may be associated with a higher risk of HF. However, sensitive analyses stratified by gender and smoking status indicated that >6 cups/d does not significantly increase the risk of HF. Additionally, the type of coffee was found to significant impact on the incidence of HF (P < 0.05). In this large cohort of UK adults, moderate coffee consumption may reduce risk of HF incidence. •Moderate coffee intake could reduce the risk of HF, but excessive coffee intake has no such effect.•In the subgroup analysis by gender and smoking, consuming >6 cups/day of coffee on HF was not statistically significant.•Different types of coffee have different effects on HF incidence and ground coffee can greatest reduces the risk of HF.